The impact of price on Potato consumption in the USA - Akter, Salma; Islam, Mohammad Raijul; Hasan, Fakhrul (Journal of Economics and Business Letters, 2022)
In this research paper we conduct our research using an econometrical analysis. In this research paper we mainly use previous economic theory, where we can find that if price increase then the demand of the good will declined automatically. This theory is more or less true for all kind of price and demand equation, it’s not different in this paper as well, but in this paper using USA potato consumption data we show that when price increase consumers always tend to reduce their potato consumptions as well, even though potato is one of the main stable sources of carbohydrate for US population. To conduct this research paper, we use data starting from 1970 till 2019.